PLAY AS A PEDAGOGICAL TOOL: PLAY IN EARLY CHILDHOOD EDUCATION - Pedro, Cleide Martins; Soares, Marcia Ap. Rodrigues; de Oliveira, Maria Inês Seredônio; Marcello, Renata; Simon, Viviane Ap. (Seven Editora, 2026)
This article analyzes the importance of play in the integral development of children and in the playful experiences they lead in Early Childhood Education, highlighting playfulness through games, pretend play, music, and stories as a central element that promotes natural, enjoyable, and meaningful learning. This study addresses the main areas of child development: cognitive, linguistic, motor, socio-emotional, moral, and creative-expressive, understanding playfulness as an indispensable pedagogical tool in the school routine. The objective is to reflect on the relevance of playfulness in teaching practice and to understand how games and play effectively contribute to children’s cognitive, social, emotional, and motor development. This is a bibliographic research study that demonstrates that play not only favors the active construction of knowledge but also strengthens social interactions, stimulates creativity, and develops autonomy. It is also a study that respects the stages of children's development, ensuring their integral development in the physical, cognitive, social, and emotional dimensions. It is concluded that the teacher plays a fundamental role in the intentional mediation of playful experiences, planning activities that enhance meaningful learning.